Reconstructing Indonesian Nationalism: From the Youth Pledge to the Digital Age - Beatrix Nino Funay Funay; Rosalinda Ina Tulit Tulit; Maria Felisitas Suan Suan; Yohanes Pemandi Banase Banase; Bakic Imanuel Aleut Aleut; Anjulin Y. Kamlasi Kamlasi; Daud Y. Nassa Nassa (Jurnal Kewarganegaraan, 2026)
This study examines the reconstruction of Indonesian nationalism within the framework of historical dialectics, spanning from the 1928 Youth Pledge to the dynamics of the contemporary digital era. Drawing on the concept of imagined communities, nationalism is understood as a social construct that undergoes continuous reformulation in tandem with political, cultural, and technological transformations. Through a historical-critical approach and critical discourse analysis, this study identifies three main dialectical phases: (1) the pre-independence phase of national identity formation, characterized by a collective consciousness that transcends ethnicity and language; (2) the post-independence consolidation phase, characterized by tensions between primordialist nationalism and civic nationalism; and (3) the recontextualization phase in the digital era, presenting a paradox between the strengthening of virtual solidarity and the fragmentation of identity. The research findings indicate that contemporary Indonesian nationalism requires a paradigmatic reconstruction grounded in the values of Bhinneka Tunggal Ika as an epistemological foundation, while also being responsive to the disruptive pressures of digital globalization. The theoretical implications of this study enrich the study of nationalism in postcolonial developing countries and provide practical relevance for the formulation of policies to strengthen national identity.